A review of the current status of induced seismicity monitoring for hydraulic fracturing in unconventional tight oil and gas reservoirs. (15th April 2019) - Li, Lei; Tan, Jingqiang; Wood, David A.; Zhao, Zhengguang; Becker, Dirk; Lyu, Qiao; Shu, Biao; Chen, Haichao
Abstract: During the past decades, significant progress has been made in the development of induced seismicity monitoring for related human activities. Hydraulic fracturing and induced seismicity monitoring are operating procedures for safe and effective production of oil and gas from unconventional resources, particularly shales. Hydraulic fracturing can induce seismicity through fluid injection and disturbance of subsurface stress in tight reservoirs. Most seismic events associated with hydraulic fracturing exhibit magnitude of Mw ≤ 3 and are referred to as microseismicity, while a few larger-magnitude earthquakes (e.g. Mw > 3) could also be induced by reactivating pre-existing faults. Here, we review the current status of research concerning induced seismicity monitoring for shale hydraulic fracturing. Induced seismicity contains information relating to important subsurface characteristics, e.g. rock failure potential and seismogenic zones. Microseismic monitoring is essential for reservoir characterization, e.g. fracture geometry delineation and reservoir geomechanical analysis. It is carried out with advanced acquisition, processing, and interpretation techniques, while larger-magnitude earthquakes are mainly exploited for potential geohazard management and mitigation. Challenges and prospects associated with multi-disciplines for future research and applications of induced seismicity monitoring are identified, and it contributes to achieve safe and efficient unconventional (tight) oil and gas resource exploitation.